Management of patients with autoimmune liver diseases on the basis of the latest EASL recommendations and our own experience (lecture to a practical doctor) - Yu. M. Stepanov; S. V. Kosynska; O. V. Pavlenko (Zaporozhye State Medical University, 2018)
Autoimmune hepatitis (AIH), primary biliary cirrhosis/cholangitis (PBC), primary sclerosing cholangitis (PSC) and autoimmune cholangiopaties are the autoimmune liver diseases. These diseases are rare and remain under-explored, therefore difficult for understanding and conducting even by specialists. Aim. To provide a comprehensively modern view of autoimmune liver diseases and their features. It is important to clearly distinguish AIG, PBH, and PSC between each other. Epidemiological data indicate low prevalence of these diseases, but its growth is noted. Most of the patients are young and middle age, prevalence of the AIH and PBC is higher in women, for PSC - in men. Etiologic factors remain unknown; the role of viral-bacterial, toxic, drugs that change the immune system with forming of autoantibodies is examined. Genetic factors also may play role in pathogenesis of these diseases. Diagnostics of autoimmune liver diseases are based on specific signs. AIH can proceed as acute or chronic hepatitis, cirrhosis or fulminant hepatic-cellular insufficiency, but also can be asymptomatic for a long time. For PBC and PSC, the clinic of cholestasis is characterized by skin itch, jaundice, skin changes. In later stages, a picture of cirrhosis develops. Hepatic tests in patients with AIH are characterized by predominance of cytolysis that can reach high values, and for PBC and PSC - cholestasis with high alkaline phosphatase and GGTP. Diagnostics with specific markers of autoimmune liver diseases are crucial for our country. AIH is characterized by detection of ANA, SMA, anti-LKM, anti-SLA, anti-LP anti-LC1, ASGP-R, and increased level of IgG. A highly specific PBC marker is AMA-M2, while p-ANCA can be determined in PSC. Among the visualizing methods of the hepatobiliary system, MRCP was identified as an accurate method for evaluating the duct system in PSC and liver elastography for evaluating the degree of fibrosis.Treatment of autoimmune liver diseases, according to the latest EASL recommendations, includes immunosuppressive therapy with hormones, azathioprine, other cytostatics, UDCA. Since the data of evidence-based medicine are limited, it is believed that an expert opinion can be crucial for the treatment of such patients. Clinical examples showing the features of management of autoimmune liver diseases are given in this article. Conclusions. Diagnosis and treatment of autoimmune liver diseases are a complex process. In this case, the latest modern recommendations can considerably help, at the same time, the clinical experience of the doctor and the patient's individual data still matter.